Pelatihan Mengolah Data dengan Aplikasi Visualisasi Data Tableau pada JPRMI - Eko Setia Setia Budi; Eva Zuraidah; Ipin Sugiyarto; Besus Maula Sulthon; Siti Indriane Maebari; Meyti Lestari; Prista Eriyanti; Said Ahmadi; Sindi Dwi Wahyuni (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Karang Taruna is a social organization as a forum and means of development for every member of the community who grows and develops on the basis of awareness and social responsibility from and for the community, especially the younger generation in the region, especially engaged in social welfare businesses. Meanwhile, the membership of DKI Jakarta Mosque Youth and Youth Network (JPRMI), hereinafter referred to as DKI Jakarta Mosque Youth and Youth Network (JPRMI) is every member of the community. Limited understanding of the management and processing of quite large data or big data in optimizing the JPRMI management environment. The data used is the JPRMI DKI Jakarta membership information system database. Therefore, because of that, Nusa Mandiri University carried out Community Service in the form of Data Management and Processing Training on the Tableu Visualization Application at JPRMI DKI Jakarta. With this training, it can help DKI Jakarta Mosque Youth and Youth (JPRMI) in managing and processing data with the tableu visualization application. The results of this community service with the results of the questionnaire obtained and obtained by producing r count > r table, the overall results of the questionnaire are valid and very good.